PENGARUH IKLIM ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN (STUDI PADA HOTEL GRAND ZURI PEKANBARU) - Sitorus, Wahyuni Daniati; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to analyze the organizational climate and organizational commitment and its effect on employee performance at Grand Zuri Hotel Pekanbaru. Climate Organization as a variable (X1), Organizational Commitment as a variable (X2), and employee performance as a variable (Y). Method in this research is descriptive and quantitative by using program of SPSS 21, where sampel used is 89 employees conducted by census and technique of data collecting through koesioner. The result of the analysis using the test of validity, reliability test, test of determination, simple linear regression test, multiple linear regression test, t test and F test so that it can be concluded that organizational climate has significant effect to employee performance at Hotel Grand Zuri Pekanbaru, Employee performance at Grand Zuri Hotel Pekanbaru, and organizational climate and organizational commitment have a significant effect on employee performance at Hotel Grand Zuri Pekanbaru. Keywords: Organizational Climate, Organizational Commitment, and Employee Performance.